Psychosocial health of adolescents in relation to underweight, overweight/obese status: the EU NET ADB survey - Drosopoulou, Georgia; Sergentanis, Theodoros N; Mastorakos, Georgios; Vlachopapadopoulou, Elpis; Michalacos, Stefanos; Tzavara, Chara; Bacopoulou, Flora; Psaltopoulou, Theodora; Tsitsika, Artemis (European Journal of Public Health, 2020)
Abstract Background Both deviations from normal weight, namely, underweight and overweight/obese status, have been inversely associated with psychosocial health in adolescents. This study aimed to examine the relationship between psychosocial health and body mass index (BMI) among adolescents in five European countries, while assessing the effect of sociodemographic variables. Methods A cross-sectional school-based study of adolescents aged 14–17.9 years was conducted in the framework of the European Network for Adolescent Addictive Behavior survey. Self-reported questionnaires from Greece, Iceland, the Netherlands, Romania and Spain were used for the current analysis. Associations between Youth Self-Report (YSR) scales and BMI status were investigated by multiple logistic regression analysis. The effect of sociodemographic variables was also measured. Results Τhe sample consisted of 7005 adolescents aged 14–17.9 years. Borderline/clinical scores on some YSR scales were independently associated with overweight/obesity, specifically total problems (OR = 1.52, 95% CI: 1.18–1.96), internalizing ( OR = 1.48, 95% CI: 1.16–1.91), externalizing (OR = 1.36, 95% CI: 1.10–1.68), social (OR = 1.67, 95% CI: 1.19–2.35) and thought problems (OR = 1.62, 95% CI: 1.20–2.20). Among subscales, overweight/obesity specifically correlated with anxiety/depression (OR = 1.83, 95% CI: 1.33–2.51), withdrawal/depression (OR = 1.58, 95% CI: 1.02–2.48) and rule-breaking behavior (OR = 1.55, 95% CI: 1.15–2.08). Underweight was associated with problems on activities (OR = 1.31, 95% CI: 1.01–1.68) and withdrawal/depression (OR = 1.95, 95% CI: 1.27–3.01). Conclusions Lower levels of psychosocial health are associated with both deviations from normal weight. These findings suggest the need for health policies that target health habits and lifestyle, as well as positive attitudes towards the body image, with respect to the different psychosocial characteristics of each body weight status category.